Staphylococcus pettenkoferi Bacteremia in an American Intensive Care Unit. (29th September 2021) - Strong, Cameron; Cosiano, Michael; Cabezas, Melanie; Barwatt, J. W.; Tillekeratne, L. Gayani
Abstract : Coagulase-negative staphylococci (CoNS) are considered the most common cause of nosocomial bloodstream infections; yet, these species are frequently designated as contaminants in the absence of systemic signs and symptoms of infection. Immunocompromised patients or those with prosthetic devices are at increased risk for clinically significant bacteremia. With the advent of matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) in clinical practice, there has been improved specificity of CoNS isolate identification and further elucidation of underrecognized pathogenic species. Staphylococcus pettenkoferi was a novel CoNS species first identified in 2002 and thought to be misdiagnosed as other CoNS due to limitations in biochemical identification. There is increasing identification of S. pettenkoferi isolates; however, there are limited case reports of clinically significant S. pettenkoferi bacteremia and no reported cases within the United States. We present the first known case of S. pettenkoferi from an American intensive care unit.